Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7759/cureus.5279
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Reperfusion Injury: Case Report, Review of the Literature, and Future Treatment Strategies

Abstract: A rare complication of cervical spine decompression is acute paralysis following the procedure. This neurologic deficit is thought to be due to reperfusion injury of a chronically ischemic spinal cord and is referred to as "white cord syndrome" given the pathognomonic finding of hyperintensity on T2-weighted MRI. Three prior cases have been reported. We present a case of transient quadriplegia following posterior cervical decompression.A 41-year-old male with cervical spondylotic myelopathy presented with bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The most widely accepted pathophysiological mechanism underlying ‘white cord syndrome’ is the sudden expansion of the chronically compressed cord and subsequent exposure to a rush of blood supply following decompression surgery, which triggers an inflammatory cascade and releases oxygen free radicals, ultimately leading to neuronal membrane damage ( 15 , 16 ). Chin et al ( 2 ) reported the first case of ‘white cord syndrome’ in a 59-year old male with severe C5/6 disc herniation who had undergone ACDF at the C4/5 and C5/6 level.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted pathophysiological mechanism underlying ‘white cord syndrome’ is the sudden expansion of the chronically compressed cord and subsequent exposure to a rush of blood supply following decompression surgery, which triggers an inflammatory cascade and releases oxygen free radicals, ultimately leading to neuronal membrane damage ( 15 , 16 ). Chin et al ( 2 ) reported the first case of ‘white cord syndrome’ in a 59-year old male with severe C5/6 disc herniation who had undergone ACDF at the C4/5 and C5/6 level.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 - 8 ] In theory, such acute cord decompression, and re-expansion disrupts the blood-spine barrier allowing for “rush-in reperfusion”, a “…triggered cascade of reperfusion injuries…”, and potentially, “…oxygen-derived free radical damage” [ Table 1 ]. [ 2 ] Other etiologies include; small artery or anterior spinal artery occlusion, “…microthrombi, and altered perfusion due to internal recoil of the spinal architecture following decompression”, “… direct trauma from blood flow itself or by the oxygen free radicals…”, or “…lipid peroxidation of the neuronal membrane…as a main cause in the secondary injury-induced degenerative cascade.”[ 1 - 5 , 7 , 8 ] In a rat model, RPI/WCS resulted in the “grey matter …(being)..dislodged when acute cord compression was “released”. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…in their 2019 study also acknowledged that RPI/WCS was a “rare complication of cervical spine decompression…”, and further observed it had been reported in just 3 prior cases. [ 7 ] Critically, however, the two individual cases respectively reported by Bailey et al . and Chin et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations